Analisis Perilaku Pangandrau Suku Dayak Maanyan Dalam Kegiatan Kematian Di Desa Sei Paken Kabupaten Barito Selatan - Josep Harianja; Yetrie Ludang; Eli Karliani (Jurnal Ilmiah Kanderang Tingang, 2026)
Death traditions among the Dayak Maanyan community possess strong social and cultural significance, one of which is manifested through pangandrau behavior. Pangandrau represents a form of social involvement by the community in the sequence of death rituals, reflecting the values of mutual cooperation, solidarity, and respect for the spirits of the deceased. This study aims to analyze the pangandrau behavior of the Dayak Maanyan tribe in death-related activities in Sei Paken Village, South Barito Regency. The research employs a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of traditional leaders, bereaved families, and community members directly involved in the implementation of pangandrau. The findings indicate that pangandrau behavior functions not only as a form of labor and material assistance but also as a medium for the transmission of cultural values, the strengthening of social relationships, and an expression of the community’s moral responsibility. Pangandrau serves as a symbol of social solidarity that continues to persist despite undergoing adaptations in response to contemporary developments.